2005
DOI: 10.1111/j.1365-2389.2005.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Total and soluble fluorine concentrations in relation to properties of soils in New Zealand

Abstract: Summary Soil fluorine (F) concentrations continue to increase in agricultural soils receiving regular applications of phosphatic fertilizer. Continued accumulation of soil F poses a risk to grazing ruminants and may pose a future risk to groundwater quality. This paper examines the range of total F (Ft) concentrations and forms of soluble F species and their relationship to selected soil properties in New Zealand agricultural soils. The Ft and soluble F (soil F extracted with water (Fwater) and 0.01 m KCl (FKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 33 publications
2
25
2
Order By: Relevance
“…A significant increase in total F was not found where the values were near or within the world's average (Helmke, 2000, Gladney and Burns, 1985; Chen et al, 1991). On the other hand, the amount of water‐soluble F showed a consistent and significant increase in the 0‐ to 30‐cm interval with increasing P application, which is presumably influenced by the decrease of soil pH ( r = −0.92, p < 0.01) (Table 6) (Pickering, 1985; Barrow and Ellis, 1986; Loganathan et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…A significant increase in total F was not found where the values were near or within the world's average (Helmke, 2000, Gladney and Burns, 1985; Chen et al, 1991). On the other hand, the amount of water‐soluble F showed a consistent and significant increase in the 0‐ to 30‐cm interval with increasing P application, which is presumably influenced by the decrease of soil pH ( r = −0.92, p < 0.01) (Table 6) (Pickering, 1985; Barrow and Ellis, 1986; Loganathan et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Adriano (2001) reported that in soils where the Cd is present at background level the residual Cd fraction is usually dominant, whereas in most highly contaminated soils this fraction may not account for a large proportion of the total soil Cd. On the other hand, soil aging may also lead to increases in Cd The quantity of Cd and F in soil solution represents <1% of their total soil contents (Gray et al 1999b;Loganathan et al 2006;Taylor and Percival 2001). In soil solution, Cd and F occur both as free ionic forms and complexed with other ions (see Fig.…”
Section: Cadmium and Fluorine Forms In Pastoral Soilsmentioning
confidence: 99%
“…But it should be noted that P affects the availability of F only in case of very high amounts of P in soil. Therefore, in our experiments a statistically significant increase of soluble F was detected in the both soil depths in accordance with the rates of the applied fertilizer, which presumably were induced by the decrease of soil pH (r=-0.92 p < 0.01) (Pickering, 1985;Barrow & Ellis, 1986;Loganathan et al, 2006). The significant increase of the amount of soluble F in the subsurface soil might be due to its leaching from the upper soil layer.…”
Section: )mentioning
confidence: 68%
“…They can maintain or improve crop yields, but they can also cause changes in the chemical and physical properties of the soil, both directly and indirectly (Hera & Mihaila, 1981;Acton & Gregorich, 1995;Aref & Wander, 1998;Belay et al, 2002). By affecting the basic soil properties (pH, organic C and N, cations, CEC, granulometic composition), phosphate fertilization may influence the solubility of certain elements, such as Al, F, Ca, and Mg (Lindsay, 1979;Kabata-Pendias & Pendias, 2001;Loganathan et al, 2006). On the other hand, mineral phosphate fertilizer could provide an abundance of available phosphorus in soil and increase the efficiency of metal-phosphate mineral formation (Ma et al, 1993;Berti & Cunningham, 1997;Hettiarachhchi et al, 1997;Cooper et al, 1998).…”
Section: Soil Agrochemical Propertiesmentioning
confidence: 99%